1998
DOI: 10.1007/s004230050159
|View full text |Cite
|
Sign up to set email alerts
|

The clonality of nodules in recurrent goiters at second surgery

Abstract: The finding that nodules in recurrent goiters are predominantly polyclonal suggests that these lesions have their origin in a de novo proliferation of different cohorts of thyrocytes due to unknown growth stimulating molecular events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 5 publications
0
10
0
1
Order By: Relevance
“…In these lesions, the presence of a TSH receptor mutation may be important (Krohn et al 1998): 10/11 cases showed monoclonality on HUMARA analysis, but only 6/12 toxic nodules with no TSH receptor mutation are clonal, raising the possibility that during thyroid hyperplasia a cell with a mutation at this locus leads to the initiation of autonomous growth. In recurrent goitres, nodules are predominantly polyclonal (Harrer et al 1998a). In several studies of clonality in multinodular goitre, the proportion of clonal nodules varies, and it is clear that clonal and polyclonal nodules can coexist in the same gland (Namba et al 1990;Bamburger et al 1993;Kim et al 1998), with no apparent correlation with morphology, although clonal nodules might be larger (Kim et al 1998).…”
Section: Current Statusmentioning
confidence: 99%
“…In these lesions, the presence of a TSH receptor mutation may be important (Krohn et al 1998): 10/11 cases showed monoclonality on HUMARA analysis, but only 6/12 toxic nodules with no TSH receptor mutation are clonal, raising the possibility that during thyroid hyperplasia a cell with a mutation at this locus leads to the initiation of autonomous growth. In recurrent goitres, nodules are predominantly polyclonal (Harrer et al 1998a). In several studies of clonality in multinodular goitre, the proportion of clonal nodules varies, and it is clear that clonal and polyclonal nodules can coexist in the same gland (Namba et al 1990;Bamburger et al 1993;Kim et al 1998), with no apparent correlation with morphology, although clonal nodules might be larger (Kim et al 1998).…”
Section: Current Statusmentioning
confidence: 99%
“…Some studies showed that in multinodular goitres clonal and polyclonal nodules coexist. Interestingly, nodules in recurrent goitres are predominantly polyclonal, while many thyroid cancers are polyclonal [22][23][24]. The collected data suggest that both benign and malignant nodules have their origin in a de novo proliferation of different cohorts of thyrocytes supporting the presence of subtle alterations within the clinically and sonographically normal perinodular tissue.…”
Section: Discussionmentioning
confidence: 79%
“…Prior studies have used X-inactivation (HUMARA) analyses to prove that the patch size in thyroid is actually quite large. 32,33 And, in fact, nodules from nodular goiter can have evidence of monoclonal origin. 34 Thus, we do know that single cells can be progenitors for fairly large nodular areas within the thyroid.…”
Section: Discussionmentioning
confidence: 99%